Ultrasound- guided microwave ablation for symptomatic breast cysts: early outcomes and clinical implications - Huynh, Khanh Quang; Nguyen, Phat Thanh; Nguyen, Khoi Van (Frontiers in Surgery, 2025)
BackgroundBreast cysts are more common in premenopausal women (61.5%), particularly between ages 35–50. Microwave ablation (MWA) has shown advantages in treating symptomatic cysts.ObjectiveTo evaluate early outcomes of ultrasound-guided MWA for breast cysts at the Breast Unit of Cho Ray Hospital.MethodsA retrospective review was conducted on patients who underwent MWA from August 2018 to March 2020.ResultsFifty-eight patients (mean age: 45.3) were included. Simple, complicated, and complex cysts accounted for 80.0%, 16.9%, and 3.1%, respectively. The mean cyst diameter was 23.86 mm. A size reduction exceeding 90% was observed in the ablated cyst at the 6 months follow- up, with the exception of 1 cyst with mural calcification that showed no response.ConclusionMWA is a promising and safe treatment for symptomatic breast cysts, offering high success and low complication rates. Cyst mural calcification may affect treatment response and should be carefully assessed.